PENGGUNAAN MEDIA DAUN GATAL (Laportea decumana) DALAM PEMBELAJARAN IPAS MATERI STRUKTUR TUMBUHAN KELAS IV SDN 01 NABIRE - Purnamasari, Yunelsi; Yektiningtiyas, Wigati; Kusdianto; Hasirun, La Ode (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Natural and Social Science (IPAS) learning in elementary schools is expected to be contextual, meaningful, and closely connected to students’ real-life experiences. However, classroom practices often remain dominated by teacher-centered instruction and textbook-based learning, resulting in limited student participation and difficulties in understanding abstract scientific concepts, particularly those related to plant structures and their functions. This situation highlights the need for learning media that utilize local environmental resources and integrate local wisdom into the learning process. This study aimed to analyze the use of stinging nettle leaves (Laportea decumana) as a local wisdom-based learning media in IPAS learning on plant structure and function material for fourth-grade students at SDN 01 Nabire, Papua Tengah. The study also explored its contribution to student engagement, conceptual understanding, and the integration of local cultural values in science learning. This research employed a qualitative approach using a case study design. Data were collected through participatory observation, semi-structured interviews, and documentation involving the principal, classroom teacher, students, parents, and school supervisor. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the use of Laportea decumana as a learning medium increased student engagement through active observation, discussion, questioning, and exploration activities. The media also facilitated a more concrete and contextual understanding of plant structures and functions while strengthening students’ awareness of the relationship between scientific knowledge and Papuan local culture. The study concludes that local wisdom-based learning media can support more meaningful, relevant, and culturally responsive IPAS learning in elementary schools. Keywords: IPAS learning, local wisdom, Laportea decumana, plant structure, contextual learning.